Effects of chromium picolinate and biotin supplementation on insulin sensitivity and lipid profile in fat-fed, streptozotocin-treated rats - Şahin, Kazım; Onderci, M; Tuzcu, M; Ustundag, B; Cikim, G; Juturu, V; Komorowski, JR (Federation Amer Soc Exp Biol, 2006)
[Abstract Not Available]
Experimental Biology 2006 Meeting -- APR 01-05, 2006 -- San Francisco, CA